The ‘Known Unknown’: Changes in the Media over the Last Quarter Century (2000–2025) - Aczél, Petra; Veszelszki, Ágnes (Filológia.hu, 2024)
Social media, generative AI, fake news and deepfake, influencer communication. Five concepts that have shaped the media landscape and market over the last 25 years. But how do they interact to form a system for describing changes in the media platforms, channels and content? Based on a review of the relevant literature (desktop research), the paper captures and describes four dominant paradigms of change that have emerged over the past quarter century, which have profoundly and irreversibly transformed our everyday practices, habits and attitudes in and through the media. These trends are: 1. changing media messages: the rise of autonomy and virtuality; 2. changing communities and audiences: the rise of personal agency; 3. changing information: the rise of the false; 4. changing representations: the rise of the artificial. The list of four we propose can, of course, be extended and narrowed. However, it is assumed that, by summarising them, we can see more clearly the phenomena and trends that characterise our present and draw conclusions for the future.